(Po)STAC (Polycistronic SunTAg modified CRISPR) enables live-cell and fixed-cell super-resolution imaging of multiple genes. Issue 5 (23rd December 2017) - Neguembor, Maria V; Sebastian-Perez, Ruben; Aulicino, Francesco; Gomez-Garcia, Pablo A; Cosma, Maria P; Lakadamyali, Melike
Abstract: CRISPR/dCas9-based labeling has allowed direct visualization of genomic regions in living cells. However, poor labeling efficiency and signal-to-background ratio have limited its application to visualize genome organization using super-resolution microscopy. We developed (Po)STAC (Po lycistronic S unTA g modified C RISPR) by combining CRISPR/dCas9 with SunTag labeling and polycistronic vectors. (Po)STAC enhances both labeling efficiency and fluorescence signal detected from labeled loci enabling live cell imaging as well as super-resolution fixed-cell imaging of multiple genes with high spatiotemporal resolution.